Improvement of the System of Strategic Planning and Management of Organizational Changes at the Enterprise - Nian, Lingchao (Харківський національний автомобільно-дорожній університет, 2025)
The paper analyzes the theoretical foundations of strategic planning and change management, as well as examines and evaluates the performance results of LLC “FFC Persha Stolytsia”. A comprehensive algorithm for the assessment, implementation, and monitoring of organizational changes has been improved, enabling a systematic and objective evaluation of innovation potential and innovation climate and providing the enterprise with clear recommendations for strategic planning. A customer relationship management system has been developed and implemented, and a feasibility and economic assessment of the proposed recommendations has been conducted. Prospects for further research are defined as the development of strategic management tools, in particular through the application of new technologies and approaches in the context of globalization and increasing competitive pressure.
Keywords: strategic planning; change management; organizational change; innovation potential; adaptability